#### Supplement to Frege's Logic, Theorem, and Foundations for Arithmetic

## Proof of the General Principle of Induction

Assume the antecedent of the principle, eliminating the defined
notation for *HerOn*(*F*, ^{a}*R*^{+}):

Pa& ∀x,y(R^{+}(a,x) &R^{+}(a,y) &Rxy→ (Px→Py))

We want to show, for an arbitrary object *b*, that
if *R*^{+}(*a*,*b*) then *Pb*. So
assume *R*^{+}(*a*,*b*). To
show *Pb*, we appeal to Fact (7) about *R*^{+}
(in our subsection on the Weak Ancestral in §4):

Fx&R^{+}(x,y) &Her(F,R) →Fy

Instantiate the variable *F* in this Fact to the property
[λ*z* *R*^{+}(*a*,*z*)
& *Pz*] (that there is such a property is guaranteed by the
Comprehension Principle for Relations), and instantiate the variables
*x* and *y* to the objects *a* and *b*,
respectively. The result (after applying λ-Conversion) is
therefore something that we have established as true:

R^{+}(a,a) &Pa&R^{+}(a,b) &Her([λzR^{+}(a,z) &Pz],R) →

R^{+}(a,b) &Pb

So if we can establish the antecedent of this fact, we
establish *Pb*. But we know that the first conjunct is true, by the
definition of *R*^{+}. We know the second conjunct is true, by
assumption. We know that the third conjunct is true, by further
assumption. So if we can establish:

Her([λzR^{+}(a,z) &Pz],R),

we are done. But, by the definition of heredity, this just means:

∀x,y[Rxy→ ((R^{+}(a,x) &Px) → (R^{+}(a,y) &Py))].

To prove this claim, we assume *Rxy* and
*R*^{+}(*a*,*x*) & *Px* (to
show: *R*^{+}(*a*,*y*)
& *Py*). But from the facts
that *R*^{+}(*a*,*x*) and *Rxy*,
it follows from Fact (3) about *R*^{+} (in our
subsection on the Weak Ancestral)
that *R*^{*}(*a*,*y*). This
implies *R*^{+}(*a*,*y*), by the definition of
*R*^{+}. But since we now
have *R*^{+}(*a*,*x*), *R*^{+}(*a*,*y*), *Rxy*,
and *Px*, it follows from the first assumption in the proof
that *Py*.